Development and evaluation of context-based laboratory activities using a laboratory in a box - FEDERIZO, RONA LYNNE ABENOJA (Archīum Ateneo, 2017)
This study used mixed-method approach to assess the efficacy of community-based learning in enhancing students' academic achievement and environmental attitudes. It involves the design and construction of community-based instructional materials, which were utilized in teaching water pollution in grade 11 senior high school students. There were two groups of students who participated in this study: (1) the traditional learning group and; (2) the community-based learning group. The two groups' abilities were matched according to their pretest scores and IQ scores. The traditional approach in teaching was applied to the traditional group, while the community-based approach was applied to the community-based learning group. After the instructional process, the two groups took post-examination to about the topic. The posttest scores served as the basis of students' learning after the discussion and intervention. The two groups also answered attitudinal questionnaires pertaining to their environmental attitudes. The independent samples t test was used to determine any significant difference between the two groups; and the paired-t test was used to measure data within groups.Results revealed an improved academic performance for both traditional learning group and community-based learning group, however, the gain score analysis showed that the community-based learning group had a statistically significant higher academic performance than the traditional learning group. In the students' environmental attitudes, the community-based learning group developed more positive environmental attitudes than the traditional learning group.In learning real environmental issues, community-based learning is a promising approach in enhancing students' conceptual understanding, and in developing more positive environmental attitudes. Moreover, this approach provides an opportunity for personal and social growth, and the development of one's sense of responsibility and accountability.